(untitled) (American Journal of Arts and Human Science, 2025)
The evolution of the tadek dance as art of the post-burial rites of the Tingguians of Nueva Era is a result of the family influence and the age of foundational learning of the identified performers of the tadek. Along with the death practices of the Tingguians during wake and burial is that the tadek dance is also performed as part of their post-burial rites. Also, the tadek dance strictly observes steps, movements and choreography in its performance as there are implications of the tadek dance on post-burial rites. Lastly, the Tingguians of Nueva Era puts so much importance and value to the tadek dance as this serves as a part of their cultural identity and cultural heritage as indigenous people .This study aims to explore the post-burial rites of the Tingguians and to document the steps, movements and choreographies observed during the performance of the tadek. This study also aims to explore the cultural relevance of the tadek dance among the Tingguians. Hence, A focused group discussion (FGD) with the participants was administered to be able to acquire the necessary data needed in the study. The participants was chosen as they are identified performers of the dance. Prior consent was secured from the National Commision on Indigenous Peoples, Office of the Mayor and a courtesy call among the tribe’s chieftain and all IP laws were observed before the conduct of the study. An interview guide formulated by the researchers which was validated by three IP members from Ilocos Norte and one professor in the Social Sciences was used during the focused group discussion (FGD). Data gathered was analyzed through a thematic analysis. To be able to analyze and interpret the data gathered, the researchers sought help from a native of the locality to translate the responses of the respondents.